Penyuluhan Tentang Makanan Sehat dan Bergizi Pada Anak Sekolah Menengah Pertama - Intan Kusumawati; Firstika Nabilla Balqis; Muhammad Ridwan; Elva Hariyani; Ananda Nurmairani Laoli; Rahmah Fadlilatu Syahadah; Latifah Mutiah Nurhidayah (Compromise Journal Community Proffesional Service Journal, 2023)
Community service activities are a series of activities that involve the community to improve skills and knowledge as well as empower the community both economically and socially. In this research, community service focuses on interactive outreach about the importance of healthy and nutritious food to students at Muhammadiyah Middle School 61 Tanjung Selamat, In this research, the counseling method was used with an Education and Training approach to students at SMP Muhammadiyah 61 involving 50 students in grades 8 c and d. The results of this activity show a positive impact in increasing students’ knowledge and understanding regarding healthy and nutritious food. In the aspect of knowledge about Healthy and Nutritious Food there has been an increase of 56%, students are better able to know what healthy and nutritious food is and its purpose. Why we should eat healthy and nutritious food. Furthermore, knowledge about Healthy and Nutritious Food Components has increased by 74% where students are able to identify important components in healthy food such as protein, fat, carbohydrates, fiber and vitamins and minerals. In conclusion, healthy and nutritious food is an indicator of clean, healthy living behavior at school. This counseling can provide practical experience to students, so that they can apply this knowledge in everyday life. And it is hoped that students will prioritize eating healthy food, especially healthy snacks, bringing lunch and breakfast every day before doing activities.